2022
DOI: 10.1097/iae.0000000000003460
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal Drusenoid Deposits and Soft Drusen

Abstract: Purpose: Soft drusen and subretinal drusenoid deposits (SDDs) characterize two pathways to advanced age-related macular degeneration (AMD), with distinct genetic risks, serum risks, and associated systemic diseases.Methods: One hundred and twenty-six subjects with AMD were classified as SDD (with or without soft drusen) or non-SDD (drusen only) by retinal imaging, with serum risks, genetic testing, and histories of cardiovascular disease (CVD) and stroke.Results: There were 62 subjects with SDD and 64 non-SDD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Recent scientific investigations have been devoted to exploring the subretinal drusenoid deposit as a critical factor linking AMD and ASCVD. In a study conducted by Thomson et al,52 subretinal drusenoid deposits were found to have a robust association with CHD and stroke, whereas no such association was observed for drusen. A cross-sectional study of 200 well-characterized intermediate patients with AMD also suggested that specific high-risk vascular diseases were even more strongly associated with subretinal drusenoid deposits than drusen 53.…”
Section: Discussionmentioning
confidence: 91%
“…Recent scientific investigations have been devoted to exploring the subretinal drusenoid deposit as a critical factor linking AMD and ASCVD. In a study conducted by Thomson et al,52 subretinal drusenoid deposits were found to have a robust association with CHD and stroke, whereas no such association was observed for drusen. A cross-sectional study of 200 well-characterized intermediate patients with AMD also suggested that specific high-risk vascular diseases were even more strongly associated with subretinal drusenoid deposits than drusen 53.…”
Section: Discussionmentioning
confidence: 91%
“…From a cardiometabolic perspective, while a large body of evidence supports the value of retinal microvasculature metrics from fundus photography (27,30,(71)(72)(73) in determining cardiometabolic risk, few publications examine the associations between different layers from retinal OCT data and cardiovascular events and/or risk factors. A recent study in a small cohort identified that subretinal drusenoid deposits, one of the pathways to advanced AMD, are associated with cardiovascular disease and stroke (74). Several other studies have similarly identified associations between AMD and risk of heart failure (75) and cardiometabolic disease (76).…”
Section: Discussionmentioning
confidence: 99%
“…The incident analyses also corroborated these findings showing that a thinner PS layer is associated with future incident cardiometabolic, renal, and pulmonary disease, suggesting that individuals with thinner PS layers already have some existing undiagnosed preclinical cardiometabolic or pulmonary disease (e.g., prediabetes and metabolic disease) that makes them at higher risk for becoming diagnosed with incident disease. A recent study in a small cohort identified that subretinal drusenoid deposits, one of the pathways to advanced AMD, are associated with cardiovascular disease and stroke ( 39 ). Several other studies have similarly identified associations between AMD and risk of heart failure ( 40 ) and cardiometabolic disease ( 41 ).…”
Section: Discussionmentioning
confidence: 99%